Vibration absorption performance of membrane-type metamaterial on a thin plate - Gao, Cong; Halim, Dunant; Rudd, Chris (Institute of Noise Control Engineering, 2019)
This work aims to investigate the vibration absorption performance of membrane-type metamaterial on a thin plate. Simulation work was conducted on membrane-type metamaterial using membrane resonators with various configurations of decorated masses. The bandgap property of membrane-type metamaterial with multiple masses was investigated. It was found that a slight adjustment of location for the decorated masses could result in a 45 Hz change of the membrane-type metamaterial bandgap location. Through the simulation work, the vibration transmissibility of a thin plate attached with membrane resonators was studied and it was showed that this membrane-type resonator could effectively suppress the vibration of a thin plate.